CFD Simulation of Two Tandem Floating Offshore Wind Turbines in Surge Motion. Issue 5 (September 2020) - Rezaeiha, Abdolrahim; Micallef, Daniel
Abstract: High-fidelity unsteady Reynolds-averaged Navier-Stokes (URANS) CFD simulation is employed to investigate the variations in the power performance of two tandem in-line floating offshore horizontal axis wind turbines for the scenario in which the upstream rotor is oscillating in surge motion and the downstream rotor is positioned in a distance of 3D (D: turbine diameter) and is stationary. The rotors are the NREL-5MW reference turbine. The platform surge period and wave amplitude are 9 s and 1.02 m, respectively. The results are presented for 100 full surge periods. It is found that the surge motion of the upstream rotor results in: (i) sinusoidal fluctuations in the power and thrust coefficients (CP and C T ) of the upstream rotor with a standard deviation (std) of 9.7% and 5.5%, respectively; (ii) such fluctuations in CP and CT are less regular with a std of 4.2% and 2.8% for the downstream rotor, respectively. A low-frequency oscillating mode with a period nearly 10 times the surge period is also observed for the downstream rotor. The mean Cp and Ct of the downstream rotor are 28.9% and 38.5% of the upstream one.